Pragmatics In Nominal Compounding (Al-Mansour Journal, 2022)
The present paper sheds light on the interdependent relation between compounding and pragmatics. Different approaches toanalyze compounds are examined .These are descriptive, semantic, typological, generativist, and pragmatic ;all confirmed that the set of compounding semantic relations is infinite. The reference to pragmatic information is crucial , since it leads both the speaker andhearer to question if compound interpretation can be formalized at all. The most important problems in any pragmatic theory tocompounding are redundant compounds , indirect compounding relations , and lack of generalization. Pragmatics and extralinguisticknowledge help the speaker and the listener reduce multiple ambiguities and inherent vagueness of these compound forms inways that a purely grammatical/semantic description does not. Pragmatic theories stress the importance of context in compoundinterpretation , social , cultural and stylistic background of the speaker and hearer.
Keywords: Pragmatics; compounding; grammatical/semantic